PENGEMBANGAN BALAI PENYULUHAN PERTANIAN (BPP) BANGUNTAPAN SEBAGAI MODEL - Sujono, Sujono (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2016)
This study aims to determine the agricultural extension programme facilitation, agricultural extension facilitation, facilitation of information, the main institutional actors and businessmen, human resources and Agricultural Extension Workers (PPL, Penyuluh Pertanian Lapangan) facilities in Banguntapan Institution of Agricultural Extension (BPP, Balai Penyuluhan Pertanian) as a model. The method used are observation, interview and questionnaire. The results showed that the Agricultural Extension Center as a model to be supported in their programme in Banguntapan were: counselling, counselling facilities, information facilities, institutional, PPL resources, and supporting devices facilities. The Banguntapan Institution of Agricultural Extension still requires necessary improvement to become the Model for Extension, the same applied for the quality of human resources, THL, and self-help. The Institutions infrastructure still needed improvement and its readiness as a model needs support from its apparatus. Financial support for the EMB Banguntapan was prerequisite as the model is still lacking for the operational management and operational of BPP. Improvement was needed in terms of the quality of Extension human resources, through training and collaborating with other relevant institutions. It should be proposed to the local government as necessities for the development of BPPs extension activities and management.